Análise da maturidade da gestão da qualidade e do desempenho organizacional em laboratórios de ensaio e calibração - Ribeiro, Taciane Fulcher (My University, 2025)
This study analyzes the relationship between the level of maturity of quality management and organizational performance in testing and calibration laboratories. The research seeks to fill a theoretical gap by proposing and applying a specific maturity model for this context, structured based on the requirements of ISO/IEC 17025:2017, the principles of organizational performance evaluation from ISO 9004:2019, and key performance indicators (KPIs) focused on strategic dimensions such as operational efficiency, market positioning, and economic-financial performance. The methodological approach is based on the concept of progressive maturity in stages, adapted from Crosby?s (1979) Quality Management Maturity Grid (QMMG). Through the application of a structured questionnaire (survey), information was collected on quality management practices and organizational performance in laboratories located in southern Brazil. The quantitative descriptive analysis demonstrated that higher levels of quality management maturity are positively associated with more structured performance evaluation systems, as well as with better organizational results. The results showed that laboratories accredited and/or recognized according to ISO/IEC 17025:2017 presented a significantly higher level of maturity (M = 4.08; SD = 0.74) compared to non-certified laboratories (M = 2.78; SD = 0.51), t(10) = 3.586, p = 0.005. Similarly, the maturity of the performance evaluation system was higher in certified laboratories (M = 3.60; SD = 0.55) than in non-certified ones (M = 2.14; SD = 0.43), t(10) = 3.198, p = 0.010. Furthermore, a strong and statistically significant positive correlation was found between the maturity of quality management and the maturity of the performance evaluation system (r = 0.870; p < 0.001). In addition to the theoretical contribution, the proposed model represents a practical diagnostic tool with the potential to support laboratories in identifying gaps and making strategic decisions, fostering quality management that is more aligned with long-term organizational objectives. [resumo fornecido pelo autor]
Este estudo analisa a relação entre o nível de maturidade da gestão da qualidade e o desempenho organizacional em laboratórios de ensaio e calibração. A pesquisa busca preencher uma lacuna teórica ao propor e aplicar um modelo de maturidade específico para esse contexto, estruturado com base nos requisitos da ISO/IEC 17025:2017, nos princípios de avaliação do desempenho organizacional da ISO 9004:2019 e em indicadores-chave de desempenho (KPIs) voltados a dimensões estratégicas, como eficiência operacional, posicionamento de mercado e desempenho econômico-financeiro. A abordagem metodológica fundamenta-se no conceito de maturidade progressiva em estágios, adaptado do modelo Quality Management Maturity Grid (QMMG), de Crosby (1979). Com a aplicação de um questionário estruturado (survey), foram coletadas informações sobre práticas de gestão da qualidade e desempenho organizacional em laboratórios situados na região Sul do Brasil. A análise descritiva quantitativa demonstrou que níveis mais elevados de maturidade na gestão da qualidade estão positivamente associados a sistemas de avaliação de desempenho mais estruturados, bem como a melhores resultados organizacionais. Os resultados mostraram que laboratórios acreditados e/ou reconhecidos segundo a ISO/IEC 17025:2017 apresentaram nível de maturidade significativamente superior (M = 4,08; DP = 0,74) em comparação aos não certificados (M = 2,78; DP = 0,51), t(10) = 3,586, p = 0,005. De forma semelhante, a maturidade do sistema de avaliação de desempenho foi maior nos laboratórios certificados (M = 3,60; DP = 0,55) do que nos não certificados (M = 2,14; DP = 0,43), t(10) = 3,198, p = 0,010. Ademais, verificou-se uma correlação positiva forte e estatisticamente significativa entre a maturidade da gestão da qualidade e a maturidade do sistema de avaliação de desempenho (r = 0,870; p < 0,001). Além da contribuição teórica, o modelo proposto representa uma ferramenta prática de diagnóstico, com potencial para apoiar os laboratórios na identificação de lacunas e na tomada de decisões estratégicas, promovendo uma gestão da qualidade mais alinhada aos objetivos organizacionais de longo prazo. [resumo fornecido pelo autor]
Keywords: Desenvolvimento organizacional; Gestão da qualidade total; Engenharia de produção; Organizational change; Total quality management; Production engineering